2004
DOI: 10.1127/0935-1221/2004/0016-0533
|View full text |Cite
|
Sign up to set email alerts
|

Filatovite, K(Al, Zn)2(As, Si)2O8, a new mineral species from the Tolbachik volcano, Kamchatka peninsula, Russia

Abstract: Burnsite, ideally KCdCu 7 O 2 (SeO 3 ) 2 Cl 9 , occurs in a fumarole in the North Breach of the great fissure Tolbachik volcano eruption (1975Tolbachik volcano eruption ( -1976, Kamchatka Peninsula, Russia. It occurs as dark red, anhedral, equidimensional grains. Associated minerals are cotunnite, sophiite, chloromenite, georgbokiite, ilinskite and an undefined Cu-Pb selenite. Burnsite is very rare and has only been found as several dozen grains that do not exceed 0.1 mm in maximum dimension. It is very simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 17 publications
0
10
0
2
Order By: Relevance
“…In particular, this silicate forms a continuous solid solution with the arsenate feldspar filatovite with the simplified formula K[(Al, Zn) 2 (As, Si) 2 O 8 ]. This mineral was first discovered in fumaroles of the second scoria cone of the NB GTFE by Vergasova et al (2004). However, chemical variations in filatovite and an isomorphous relationship with other feldspars have not been systematically studied before our work.…”
Section: Feldsparsmentioning
confidence: 96%
See 1 more Smart Citation
“…In particular, this silicate forms a continuous solid solution with the arsenate feldspar filatovite with the simplified formula K[(Al, Zn) 2 (As, Si) 2 O 8 ]. This mineral was first discovered in fumaroles of the second scoria cone of the NB GTFE by Vergasova et al (2004). However, chemical variations in filatovite and an isomorphous relationship with other feldspars have not been systematically studied before our work.…”
Section: Feldsparsmentioning
confidence: 96%
“…In previous works devoted to the mineralogy of Tolbachik fumaroles, any potassic feldspar, except for filatovite with As > Si, was considered to be orthoclase (Serafimova, 1992;Vergasova et al, 2004;Vergasova and Filatov, 2016). In publications on minerals from fumaroles of the second scoria cone of the NB GTFE we also used the name orthoclase for potassic feldspar following this "tradition" (e.g.…”
Section: Chemical and Structural Features Of The Main Fumarolic Silicmentioning
confidence: 99%
“…The species diversity in the feldspar group is due mainly to the substitutions in the extra-framework cation sites and different schemes of Al/Si-ordering at tetrahedrally coordinated sites of the framework. Until this work, only two valid minerals of the feldspar group with species-defining tetrahedral components except of Si and Al were known, namely, the borosilicate reedmergnerite Na[B 3+ Si 3 O 8 ] [32] and the alumino-arsenate filatovite K[(Al,Zn) 2 (As,Si) 2 O 8 ] [33]. They are both very rare and known from few specific geological formations.…”
Section: Discussionmentioning
confidence: 99%
“…Reedmergnerite occurs in dolomitic oil shales of the Green River formation in Utah, USA [32,34] and in peralkaline pegmatites of two alkaline complexes, Dara-i-Pioz in Tajikistan [4] and Lovozero at Kola peninsula, Russia [35]. Filatovite and intermediate members of the sanidine-filatovite solid-solution series are known only from sublimates of fumaroles at the Second scoria cone of the NB GFTE including the Arsenatnaya fumarole [20,33]. Ferrisanidine K[Fe 3+ Si 3 O 8 ] is the second, after reedmergnerite Na[B 3+ Si 3 O 8 ], natural feldspar without species-defining Al.…”
Section: Discussionmentioning
confidence: 99%
“…The partition coefficient of arsenic between sulfide and silicate melts varies as a function of oxygen fugacity; at a given temperature and FeO content, the proportion of arsenic in silicate and monosulfide melts increases with oxygen fugacity Audétat 2012, 2015). Although silicate and carbonate mineral phases do not host arsenic as a major element (Majzlan et al 2014), under conditions of low temperature, high oxygen fugacity, and low sulfur fugacity, silicates and carbonates can incorporate arsenic; for example, filatovite (K [Al, Zn] 2 (As, Si) 2 O 8 ), a variety of feldspar, has been found to be associated with volcanism in Kamchatka (Vergasova et al 2004). Charnock et al (2007) also found that arsenic was incorporated into garnet in the overgrowth of a hydrothermal vein, and Pascua et al (2005) found arsenic-enriched smectite in hydrothermal precipitates at a geothermal plant in Akita, Japan.…”
Section: Geologic Cycling Of Arsenicmentioning
confidence: 99%